Response surface-based media optimization for astaxanthin production in Corynebacterium glutamicum - Meyer, Florian; Schmitt, Ina; Wendisch, Volker F.; Henke, Nadja A. (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionAstaxanthin is a C40 carotenoid that is used in animal feeds or cosmetics. Due to its high antioxidant property it is used for, e.g., anti-aging formulations and due to its intense red color it is used, e.g., in animal feed. While about 95% of commercial astaxanthin is currently chemically synthesized from fossil sources, the interest in natural and sustainable astaxanthin is growing. Corynebacterium glutamicum, an attractive host used in large-scale processes, e.g., industrial amino acid production, has been engineered for astaxanthin production.MethodsHere, a design of experiment (DoE) approach was applied to optimize the standard minimal medium for astaxanthin production. The concentrations of carbon, nitrogen and phosphorus sources, magnesium, calcium, the iron chelator protocatechuic acid, the vitamin biotin, and the trace metals were varied and astaxanthin production was evaluated.Results and discussionBy increasing the concentration of iron and decreasing that of manganese especially, it was possible to increase astaxanthin titers from 7.9 mg L−1–39.6 mg L−1 in a micro cultivation system and from 62 mg L−1–176 mg L−1 in a fed-batch fermentation.